1994
DOI: 10.1002/jemt.1070270208
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes during meiotic maturation in mammalian oocytes: Unique aspects of the human oocyte

Abstract: This paper reviews the process of peri-ovulatory oocyte maturation and the ultrastructural organization of the human egg and compares it with that of the mouse. The main thrust of the paper is on the human, since there are several reviews on the mouse. Both preovulatory and postovulatory events at fertilization, as well as some of the aberrant features of maturation are covered. Some changes induced by oocyte culture and cooling in the human are also included. The report attempts to focus on unique features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
2
43
0
1
Order By: Relevance
“…The pits in aged fertilized mouse eggs seem similar to the "membrane-delimited craters…termed cortical crypts" observed in zebrafish eggs, structures which are described as remnants of exocytosed cortical granules (Becker and Hart, 1999). The vesicles observed here on aged eggs appear to be membrane blebs, in agreement with reports of membrane blebbing, abnormally shaped microvilli, and release of cytoplasmic fragments observed in aged rabbit, hamster and human eggs (Longo, 1974a, Longo, 1974b, Sathananthan, 1994, and similar to membrane blebs observed in mouse eggs treated with the microfilament disruptor cytochalasin B (Longo and Chen, 1985). Interestingly, cytoplasmic and DNA fragmentation has been observed in aged eggs activated with an extract of soluble sperm (Gordo et al, 2002, Gordo et al, 2000, suggesting that sperm-induced Ca 2+ signaling can trigger apoptosis-like responses in aged eggs; the membrane abnormalities observed here in fertilized aged eggs may be linked with the way an aged eggs responds to increased cytosolic Ca 2+ , clearly differing from the responses in a young, healthy egg.…”
Section: A B a Bsupporting
confidence: 90%
See 2 more Smart Citations
“…The pits in aged fertilized mouse eggs seem similar to the "membrane-delimited craters…termed cortical crypts" observed in zebrafish eggs, structures which are described as remnants of exocytosed cortical granules (Becker and Hart, 1999). The vesicles observed here on aged eggs appear to be membrane blebs, in agreement with reports of membrane blebbing, abnormally shaped microvilli, and release of cytoplasmic fragments observed in aged rabbit, hamster and human eggs (Longo, 1974a, Longo, 1974b, Sathananthan, 1994, and similar to membrane blebs observed in mouse eggs treated with the microfilament disruptor cytochalasin B (Longo and Chen, 1985). Interestingly, cytoplasmic and DNA fragmentation has been observed in aged eggs activated with an extract of soluble sperm (Gordo et al, 2002, Gordo et al, 2000, suggesting that sperm-induced Ca 2+ signaling can trigger apoptosis-like responses in aged eggs; the membrane abnormalities observed here in fertilized aged eggs may be linked with the way an aged eggs responds to increased cytosolic Ca 2+ , clearly differing from the responses in a young, healthy egg.…”
Section: A B a Bsupporting
confidence: 90%
“…This polarity in the mature egg develops during oocyte maturation. The surface of pre-ovulatory prophase I oocytes in rodents and in humans is characterized by uniformly distributed microvilli (Sathananthan, 1994). As the oocyte progresses from prophase I arrest into meiosis I, the meiotic spindle forms in the central position (where the germinal vesicle was localized), and then migrates to a more peripheral location, such that the spindle is now positioned for the asymmetric cytokinesis that occurs with completion of meiosis I.…”
Section: Summary Of Key Ultrastructural Findings Related To Mammalianmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid droplets interact with the elements of the cytoskeleton in the oocytes. These interactions are destroyed during cryopreservation [16,17], which causes irreversible damage to the oocyte. In the present study, the lipid contents were expressed both per oocyte and per volume as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…One such event involves specialized organelles, known as cortical granules. In response to Ca 2þ rise, cortical granules migrate toward the oolemma to release their enzyme contents into the perivitelline space in a process known as the cortical reaction (Sathananthan et al, 1985;Sathananthan, 1994). Cortical granule release results in alteration of zona pellucidae, cleaving ZP2 to ZP2f, and modifying ZP3, thus preventing further sperm binding and polyspermic penetration (Ducibella et al, 1990;Schroeder et al, 1990).…”
Section: Cortical Granule Reactionmentioning
confidence: 99%